Supercomputing for molecular dynamics simulations : handling multi-trillion particles in nanofluidics /: handling multi-trillion particles in nanofluidics. ([2015]) - Heinecke, Alexander; Eckhardt, Wolfgang; Horsch, Martin; Bungartz, H.-J (Hans-Joachim)
No abstract available